SHABA DIARY: A TRIP TO REDISCOVER THE 'KATANGA' GUITAR STYLES AND SONGS OF THE 1950s AND '60s, by John Low, Acta Ethnologica et Linguistica Nr.54, Ed. Engelbert Stiglmayr, Series Musicologica 4 Series Africana 16, Wien-Fohrenau, 1982. Co-eds: Franz Fodermayr, Anna Hohenwart-Gerlachstein, Gerhard Kubik, 125 pp., photo, music examples, bibliography, discography. - Rycroft, David K. (International Library of African Music, 1996)
pages: 145-147
Keywords: African Music